PDL1 Fusion Protein Protects Against Experimental Cerebral Malaria via Repressing Over-Reactive CD8+ T Cell Responses - Wang, Jun; Li, Yue; Shen, Yan; Liang, Jiao; Li, Yinghui; Huang, Yuxiao; Liu, Xuewu; Jiang, Dongbo; Yang, Shuya; Zhao, Ya; Yang, Kun (Frontiers in Immunology, 2019)
Cerebral malaria (CM), mainly caused by Plasmodium falciparum (P. f.), is one of the most lethal complications of severe malaria. As immunopathology mediated by brain-infiltrating CD8+ T cells is the major pathogenesis of CM, there is no safe and efficient treatment clinically focused on CD8+ T cells, new methods are needed to protect the host from injury. As evidence has shown that programmed death-1 (PD-1) is one of the most efficient immunomodulatory molecules, we constructed two soluble fusion proteins, PDL1-IgG1Fc and PDL2-IgG1Fc, to up-regulate the PD-1 repressive signals in innate and adaptive immune cells, including macrophages and CD8+ T cells. First, we confirmed that PD-1 signal pathway deficiency led to higher levels of CD8+ T cell proliferation and shorter survival time in PD-1-deficient (Pdcd1-/-) mice than WT mice. Second, PDL1-IgG1Fc-treated mice exhibited a more prolonged survival time than control groups. Moreover, PDL1-IgG1Fc was observed to ameliorate blood-brain barrier (BBB) disruption by limiting the over-reactive CD8+ T cell cytotoxicity during experimental cerebral malaria (ECM). Further studies found that PDL1-IgG1Fc-treated macrophages showed significant suppression in macrophage M1 polarization and their antigen presentation capability to CD8+ T cells. In conclusion, our results demonstrated that the administration of PDL1-IgG1Fc in the early stage before ECM onset has an obvious effect on the maintenance of immune microenvironment homeostasis in the brain and is deemed a promising candidate for protection against CM in the future.